Advertisement

Now, let's look at the second one:

by plugging y = 0 into the original equation 3x - y = 6, we get 3x - 0 = 6, which simplifies to 3x = 6 and gives x = 2

Just cover the y guy with your finger:

ignore the -y part of the equation 3x - y = 6 by covering it with your finger

So, we get

put the 2 in the x column next to the 0 in the y column, which shows that ( 2 , 0 ) is a point on our graph -- the x-intercept

Since we just need two points to draw the line, we're set!

the graph of a line passing through the points ( 0 , -6 ) and ( 2 , 0 )